Hubungan Pemberian Reward dan Punishment terhadap Motivasi Belajar pada Pembuatan Blus di SMK Negeri 1 Jabon - Rosa Maharani; Ratna Suhartini; Lutfiyah Hidayati; Inty Nahari (Departement of Mathematics Education, 2024)
This research began with various problems faced by students in the learning process, one of which was students' lack of motivation in achieving learning goals. Due to this problem, various methods which will be the solution to this problem, one of which is the method of providing rewards and punishments. This research aims to determine the relationship between giving rewards and punishments to learning motivation in making blouses at SMK Nergeri 1 Jabon. This research used a quantitative approach with a population of 72 students and because the sampling technique in this research used a total sampling technique, the samples taken totaled 72 respondents. The data collection technique used was a questionnaire. Meanwhile, data analysis used product moment correlation with the help of the SPSS 23 application. The results of this research show that there is a relationship between giving rewards and punishment to learning motivation. It is known that the calculated r is greater than the r table (0.490 > 0.339) and the significance value obtained is 0.000 which is smaller than 0.05